Projection of Climate Change on the Probability of Dengue Hemorrhagic Fever in North Sumatra Province - Simbolon, Theresia Grefyolin; Frida, Erna; Sinambela, Marzuki; Situmorang, Marhaposan; Humaidi, Syahrul; Darmawan, Yahya (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
Climate change is a major threat to global prosperity. The industrial revolution has occurred since 1750 to 2010 where the increase in global air temperature has reached 0.7°C. Rising temperatures and fluctuating rainfall is the identification of climate change, one of the impacts of climate change is changing the distribution of some types of mosquitoes (Aedes Aegypti).Based on the results of the analysis of the main components, a good model uses an accuracy rate of about 85% and passes the test individually and as a whole. Indonesia has a tropical climate where warm temperatures and high rainfall variability are a comfortable habitat for Aedes Aegypti mosquitoes. The breeding and life cycle of the Aedes Aegypti mosquito is directly influenced by climatic conditions. The purpose of this study is to determine the normal rainfall map, an overview of climate projection patterns, identification of characteristics of climate change in the short term (2011 – 2040), medium term (2041 – 2070) and long term (2071-2100) based on rainfall and temperature projections in North Sumatra province. Statistical methods used to determine the effect of climate on health (dengue) include statistical downscaling, delta bias correction, Principal Component Analysis, and ordinal logistic regression. The results of the ordinal logistic regression analysis show that rainfall that is suitable for dengue fever ranges from 100 - 300 mm. For North Sumatra rainfall ranges from 50 - 600 mm. In March and November is the strongest threat because of the peak with high rainfall intensity where the danger of flooding and dengue. The air temperature ranges from 24.5 - 28.5 oC, this condition is still optimal for the development of the Aedes Aegypti mosquito. The climate change projection index for the short term (2011 - 2040), medium term (2041 - 2070) and long term (2071 - 2100) shows a consistent increase with a range of 0.40C, this value will affect the acceleration of the reproduction of the Aedes aegypti mosquito as the cause of DHF. The projection probability of dengue hemorrhagic fever shows that North Sumatra Province still has a high chance of being categorized as a high risk area for dengue fever with a probability value of 0.82 - 0.99.